Mancha marrom de alternativa em tangerineira 'Dancy': Aspectos morfofisiológicos, variabilidade genética e indução de resistência - Demartelaere, Andréa Celina Ferreira (2015)
The genetic diversity of the fungus Alternaria alternata (Fr:Fr) Keissler f. sp. citri is associated with genetic and environmental factors and there has been influence on reproduction of the pathogen responsible for causing serious economic problems in fruit and tangerine seedlings 'Dancy' (Citrus tangerine hort. ex Tanaka) in the state of Paraíba. However, for the control of Alternaria brown spot (MMA) tactics are employed with in the integrated management using alternative products such as ethanol extract ironwood (Caesalpinia ferrea (Benth.)) Ducke, Chitosan® and the antagonist Trichoderma asperellum. Three experiments were conducted and the first was the in vitro test, submitting thirty isolates the V8 agar, leaf extract (EF), dextrose agar oats (ADA), potato dextrose agar (PDA) in temperature 15, 25 and 35 °C and light regimes, dark and continuous light and alternating light, incubated in BOD The mycelial growth (CM) was evaluated at 24 hour intervals up to seven days and sporulation was quantified in a Neubauer chamber and adjusted to 105 spores/mL. Then, the molecular characterization was done with 38 isolated by ISSR and genetic similarity quantified by Jaccard index. The experimental design used in Morphophysiological characterization was completely randomized in a factorial arrangement, 30 isolates, four culture media: AV, BDA, EF and V8, three light regimes: continuous light, alternating light and continuous light and three temperatures: 15, 25 and 35 °C with 12 reps, making a total of 12.960 Petri dishes considering a Petri dish by repetition. The variance analysis of isolates was performed using the F test (p ≤ 0,05). The overall averages were compared by the Scott-Knott test (p ≤ 0,05) and the other by the Tukey test (p ≤ 0,05). Statistical analyzes were performed using the software SISVAR® 5.3 and SAS/STAT® 9.3. The genetic diversity in this thirty eight isolates was determined based on the presence or absence of amplified DNA fragments of three primers and viewed on electrophoresis gels. The images were processed in BioNumerics® software for analysis of genetic similarity Jaccard. The dendrogram was obtained by the arithmetic average of the individual groups formed in data matched pairs (UPGMA). Independent of the collection site and growing conditions used, all isolates showed statistical differences in relation to mycelial growth and sporulation. The isolates of A. alternata pathotype tangerine collected from Massaranduba-PB showed high mycelial growth, sporulation and high genetic diversity compared to other tested isolates. In general, the continuous light regime at 25 °C on PDA and V8 media was ideal for the mycelial growth and sporulation of the isolated A. alternata this pathotype tangerine, however, continuous darkness among the best AV was isolated from Pratânia-SP until the seventh valuation day. All isolates showed high genetic diversity among them and there was a grouping of tendency by location shown by markers morphophysiological and molecular aspects evaluated. The second experiment was conducted in LAFIT and LAPOA, mandarin fruit 'Dancy' were disinfected and immersed in C. ferrea extract at concentrations of 0; 10; 100; 500 and 1000 μg/mL, 0,5 Chitosan®; 1,0; 1,5 to 2,0 g/L. and T. asperellum to 1010 spores/mL. After 24 h the application of with the extracts was inoculated A. alternata (105 spores/mL) in fruits. On the second day after inoculation (DAI) were performed daily the severity assessments in fruits of tangerine 'Dancy' until the last grading scale that occurred on the twelfth day and also. For the analysis of enzyme activities of phenylalanine ammonia-lyase, peroxidase and polyphenol and post-harvest fruit tangerine 'Dancy'. The design was completely randomized with 10 treatments (0; 10; 100; 500 and 1000 μg/mL of C. ferrea extract), (0,5; 1,0; 1,5 and 2,0 g/L of Chitosan®) (1010 spores/mL T. asperellum) and five replicates of five fruits, constituting an experimental unit with 250 fruit tangerine 'Dancy'. The concentrations of 500 μg/mL C. ferrea extract, 1,5 g/L Chitosan® and T. asperellum reduced the severity of MMA promoted high activity of the enzyme phenylalanine ammonia-lyase, peroxidase and polyphenol oxidase and all treatments kept the postharvest quality in fruits of tangerine 'Dancy'. The third experiment was conducted in LAFIT and LAPOA, the plants 90 days after grafting were sprayed with C. ferrea extract at concentrations of 0; 10; 100; 500 and 1000 μg/mL, placed in a humid chamber and maintained at room temperature (28 ± 2 °C). After 24 hours of spraying was carried out the inoculation of A. alternata (105 spores/mL) and after 96 hours of inoculation until the twenty third day, the incidence were made reviews, severity AUDPC and analysis of enzymatic activities. For the determination of phenylalanine ammonia-lyase activity, peroxidase and polyphenol, were taken three sheets/repeat in the first and last day after treatment application of the products. The design was completely randomized with five treatments (0; 10; 100; 500 and 1000 μg/mL of C. ferrea extract) and 25 repetitions, forming the experimental unit with 125 seedlings. In the last two experiments, regression analyzes were performed for the concentrations of C. ferrea extract the data were submitted to analysis of variance and the means compared by Dunnett test (P ≤ 0,05) in SAS® System 9.3 program. It was found that the concentrations of 100 and 500 μg/mL C. ferrea extract reduced the incidence and severity A. alternata MMA, showed low activity of the enzyme phenylalanine ammonia- lyase, however, promoted high peroxidase activity and polyphenol oxidase in leaves of tangerine 'Dancy'.